PENGELOLAAN KEDISIPLINAN GURU DI MTS NEGERI BARAKA KABUPATEN ENREKANG - Wahida, Wahida (Pascasarjana Universitas Negeri Makassar, 2017)
This study aims to find out the description of planning, implementation, supervision and supporting factors and obstacles to teacher discipline in Baraka MTs Negeri Enrekang District. This research is a research with a qualitative approach. The source of the data in this study were the principal, vice principal, teacher, and students in the Baraka District MTs. Enrekang. the results of the study show (1) the discipline planning of teachers in the State Baraka District MTs. Enrekang is done well. (2) The implementation of teacher discipline is carried out by giving reward and punishment to the teacher, this is very influential on the implementation of the discipline of teachers in schools. (3) Supervision of teacher discipline is carried out well, Supervision is carried out before activities, during activities, and after activities. This supervision is carried out continuously to ensure the implementation of discipline in accordance with the plan. (4) Factors supporting the implementation of teacher discipline management are: goals and abilities, leadership / exemplary, legal sanctions, active supervision, conditions and work environment. (5) Inhibiting factors for the implementation of the discipline management of teachers in schools, namely the presence of teachers who are unable to attend on time at school but do not provide information to the school.